Analisis Risiko Pemasaran Sayur di Tingkat Pedagang Pengumpul Kecamatan Modoinding - Lakoy, Henro Arturito; Waney, Nordy Fritsgerald Lucky; Kaunang, Rine (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
This study aims to analyze vegetable marketing risks at the intermediary trader level in Modoinding District. The method used is Failure Mode and Effect Analysis (FMEA), using a quantitative approach with 10 purposively selected traders. Risks were assessed based on Severity, Occurrence, and Detection, and calculated into RPN and RSV scores. The results show that capital risk is the most critical (average RPN 9.9), followed by price risk (RPN 8.1). Product quality and physical damage risks had lower RPN values. This study recommends improving capital access, training in risk management, and enhancing distribution infrastructure.